Economic policy response to the pandemic: From COVID-19 emergency to economic democracy - Felix R. FitzRoy; David A. Spencer (Institute of Labor Economics (IZA), 2020)
This review of UK economic policy responses to the Covid-19 crisis identifies serious problems with existing measures. We describe alternative policies which could alleviate hardship, protect business from destruction in the growing depression, facilitate recovery with full employment in a Green New Deal, and redistribute income and power with economic democracy in the workplace. Only such policies can ensure high quality work for all, the natural rights of self-determination at work, and equitable sharing of the surplus that is produced by all employees as intentional agents. The proposed reforms are opposed by the strong vested interests which currently hold most power, so mobilising popular support and achieving real change will require a long struggle, just as attaining political democracy a century ago did.
Keywords: H; J; L; 330; COVID-19; policy response; better recovery; economic democracy